Motivation and Organizational Performance in Port-based SMEs: a literature Review (LACCEI, 2024)
This study is a literature review that addresses the importance of motivation and motivational factors on the organizational performance of small and medium-sized port businesses in Guayaquil through a qualitative approach with descriptive and non-experimental scope. After the analysis, it is revealed, that motivation is a business management tool that allows to increase the level of commitment of the collaborators within the organization because the management of the production factors and the organization performance depends on them and this contributes to the achievement of strategic objectives.